Kuasa Simbolik Tokoh Blater Dalam Kontestasi Politik Lokal Di Madura: Studi Kasus Strategi Komunikasi Politik Pilkada Bangkalan 2024 - Jadid, Moh Nurul; Jupriono; Dey Prayogo (Public Administration Dept, Faculty of Social and Political Science, 2025)
This research analyzes the symbolic power of blater figures in political communication strategies during the 2024 Bangkalan Regional Head Election, particularly examining how informal actors mobilize electoral support despite minimal institutional backing. This qualitative case study employed in-depth interviews with four key informants (blater figures, village heads, political observers, and community members) alongside participatory observation of informal social spaces. Data were analyzed using Miles and Huberman's interactive model with triangulation for validity. Blater's symbolic power is constructed through the accumulation of social capital (extensive cross-class networks), cultural capital (mastery of ajhâgâ and tengka values), and economic capital (selfless generosity), which are converted into symbolic capital. Their political communication operates implicitly through informal spaces (sandur, to'otok) with simple messages like